Oxygen metabolism by endothelial nitric-oxide synthase - Gao, Ying Tong; Roman, Linda J; Martásek, Pavel; Panda, Satya Prakash; Ishimura, Yuzuru; Masters, Bettie Sue S (The Journal of biological chemistry, 2007)
Nitric-oxide synthase (NOS) catalyzes both coupled and uncoupled reactions that generate nitric oxide and reactive oxygen species. Oxygen is often the overlooked substrate, and the oxygen metabolism catalyzed by NOS has been poorly defined. In this paper we focus on the oxygen stoichiometry and effects of substrate/cofactor binding on the endothelial NOS isoform (eNOS). In the presence of both L-arginine and tetrahydrobiopterin, eNOS is highly coupled (>90%), and the measured stoichiometry of O(2)/NADPH is very close to the theoretical value. We report for the first time that the presence of L-arginine stimulates oxygen uptake by eNOS. The fact that nonhydrolyzable L-arginine analogs are not stimulatory indicates that the occurrence of the coupled reaction, rather than the accelerated uncoupled reaction, is responsible for the L-arginine-dependent stimulation. The presence of 5,6,7,8-tetrahydrobiopterin quenched the uncoupled reactions and resulted in much less reactive oxygen species formation, whereas the presence of redox-incompetent 7,8-dihydrobiopterin demonstrates little quenching effect. These results reveal different mechanisms for oxygen metabolism for eNOS as opposed to nNOS and, perhaps, partially explain their functional differences.
Keywords: Animals; Catalysis; biopteriny; Nitric Oxide Synthase Type I; katalýza; Arginine; lidé; rekombinantní proteiny; Recombinant Proteins; Reactive Oxygen Species; synthasa oxidu dusnatého, typ III; synthasa oxidu dusnatého, typ I; Oxygen; Biopterins; Nitric Oxide; nitrosaminy; reaktivní formy kyslíku; arginin; Nitric Oxide Synthase Type III; oxid dusnatý; Nitrosamines; zvířata; kyslík; Humans